Sistema web administrable y aplicación móvil de noticias e información de interés para una Institución Educativa - Herrera Celi, Wilson Bolivar; Aguirre Jaramillo, Diego Fernando (Machala; Universidad Técnica de Machala, 2024)
Currently, ICTs have been fundamentally integrated into people's daily routines; Faced with this reality, the idea of creating systems that help improve the life of society has been raised. At the Monseñor Leonidas Proaño Municipal High School, the lack of capacity of traditional media to capture the attention of the educational community represents an obstacle in the effective dissemination of information, the development of a manageable web system and a mobile application is proposed. news and information of interest. The analysis of the requirements and development stages of the system was carried out based on the SWIRL methodology. The technologies used are React, Ionic, Express.js, MySQL and Face-api; The developed solutions have two user roles: Administrator and Member, the most relevant modules are News, Viewed Publications, Publication Tracking, Login and Registration, of which the latter have facial recognition in the Web System; To evaluate the system, SEO tools and the ISO/IEC 9126 standard were used; The research has a descriptive scope, the collection of information was sought using the Systematic Literature Review Methodology; In addition, a survey was applied to collect data, the sample was 123 people out of a population of 875, belonging to the educational community. With the results obtained, it has been demonstrated that the stated hypothesis was met, since 96% of the educational community considers that the web system and mobile application allows access to the information of the Educational Institution. As the next project, the implementation of the qualifications module is proposed, in this way, parents will be able to efficiently know the academic performance of their constituents
Actualmente, las TIC se han integrado de manera fundamental en la rutina cotidiana de las personas; frente a esta realidad, se ha planteado la idea de crear sistemas que ayuden a mejorar la vida de la sociedad. En el Colegio de Bachillerato Municipal Monseñor Leonidas Proaño, la falta de capacidad de los medios tradicionales para captar la atención de la comunidad educativa representa un obstáculo en la difusión efectiva de información, se propone el desarrollo de un sistema web administrable y una aplicación móvil de noticias e información de interés. El análisis de los requisitos y las etapas de desarrollo del sistema se llevó a cabo a partir de la metodología SWIRL. Las tecnologías empleadas son React, Ionic, Express.js, MySQL y Face-api; Las soluciones desarrolladas poseen dos roles de usuario: Administrador y Miembro, los módulos más relevantes son Noticias, Publicaciones Visualizadas, Seguimiento de Publicaciones, Inicio de Sesión y Registro, de los cuales estos últimos cuentan con reconocimiento facial en el Sistema Web; Para evaluar el sistema se utilizaron herramientas SEO y la norma ISO/IEC 9126; La investigación tiene un alcance descriptivo, se buscó la recolección de información empleando la Metodología de Revisión Sistemática de Literatura; Además, se aplicó una encuesta para la recopilación de datos, la muestra fue de 123 personas de una población de 875, pertenecientes a la comunidad educativa. Con los resultados obtenidos, se ha podido demostrar que, si se cumplió con la hipótesis planteada, ya que un 96% de la comunidad educativa considera que los sistemas permiten el acceso a la información de la Institución Educativa. Como próximo proyecto, se plantea la implementación del módulo de calificaciones, de esta manera los padres de familia podrán conocer de manera eficiente el desempeño académico de sus representados
Keywords: EXPRESS; JS; IONIC; REACT; RECONOCIMIENTO FACIAL; SISTEMA WEB